A New Design and Analysis of Power Saving for IoT Gateway. Issue 3 (4th May 2022) - Chandroth, Jisi; Saxena, Navrati; Roy, Abhishek; Rastogi, Eshita
Abstract : Internet of Things (IoT) enables the connection of physical objects to the internet for exchanging information. Due to the massive number of IoT devices, cellular traffic is increasing exponentially in wireless networks. IoT devices require low latency, high reliability and massive connectivity. Fifth Generation (5G) networks are expected to provide promising solutions to meet these demands and improve the performance of IoT systems. 5G offers low latency, high reliability, and efficient data transmissions for large number of connected IoT devices. IoT systems employ gateways for efficient connectivity of various devices. Gateways have capabilities of integrating various protocols, handling data storage temporarily, analyzing the data, and transmitting that data between edge devices and cloud. IoT devices transmit data in frequent intervals, causing the gateway to be active all the time, leading to the increase in power consumption of the gateways. In this article, we focus on applying Discontinuous Reception (DRX) mechanism to IoT gateways. The proposed DRX at IoT gateways reduces the power consumption and improves the energy efficiency of IoT gateways. Our proposed work improves the energy efficiency of gateways by almost 30% compared to Relay Energy Efficiency (REE) based scheme.